A revision of the genus Aphengium Harold, 1868 (Coleoptera: Scarabaeidae: Scarabaeinae: Ateuchini) - Silva, Fernando A. B.; Vaz-De-Mello, Fernando (Zootaxa, 2015)
Aphengium Harold, a dung beetle genus endemic to the Atlantic forests of Brazil, comprises four valid species: A. sordidum Harold, 1868, A. cupreum Shipp, 1897, A. ibateguara sp. nov., A. curtum sp. nov.. In this revision of the genus each species is analyzed as follows: a detailed literature review, a diagnosis, illustrations of key morphological characters, a listing of material examined and geographic distribution. A lectotype is designated for A. sordidum, and a neotype for A. cupreum.